2013
DOI: 10.1038/bjc.2013.176
|View full text |Cite
|
Sign up to set email alerts
|

Sox11 expression in astrocytic gliomas: correlation with nestin/c-Met/IDH1-R132H expression phenotypes, p-Stat-3 and survival

Abstract: Background:Sox11 is a transcription factor expressed in foetal and neoplastic brain tissue, including gliomas. It has been shown to suppress the tumourigenicity of glioma stem cells in vivo, thereby being hypothesised to function as a tumour suppressor.Methods:We investigated the expression of Sox11 in 132 diffuse astrocytomas in relation to the regulator cell marker nestin, c-Met and IDH1-R132H, which have shown to be differentially expressed among the molecular subgroups of malignant gliomas, as well as to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
(87 reference statements)
1
19
0
Order By: Relevance
“…HCC is one of the most common and aggressive malignancies worldwide and is often accompanied by a high recurrence rate and poor prognosis after surgery, which are mainly attributed to the proliferative, invasive, and migratory capabilities of HCC cells . SOX11 is recognized as a type of transcription factor that belongs to the HMG box protein superfamily . The function of SOX11 is mainly associated with neural development and organogenesis during embryonic development .…”
Section: Discussionmentioning
confidence: 99%
“…HCC is one of the most common and aggressive malignancies worldwide and is often accompanied by a high recurrence rate and poor prognosis after surgery, which are mainly attributed to the proliferative, invasive, and migratory capabilities of HCC cells . SOX11 is recognized as a type of transcription factor that belongs to the HMG box protein superfamily . The function of SOX11 is mainly associated with neural development and organogenesis during embryonic development .…”
Section: Discussionmentioning
confidence: 99%
“…SOX‐11 is known to be expressed in hematopoietic and glial malignancies such as mantle cell lymphoma and astrocytic gliomas; however, its role in solid tumors such as SPNs is still unknown. In a recent publication, Li et al reported that according to a microarray analysis, SOX‐11 was found to be exclusively expressed in SPNs in comparison with normal pancreas, pancreatic adenocarcinomas, and pancreatic NETs .…”
Section: Discussionmentioning
confidence: 99%
“…SOX‐11 is localized on chromosome 2p25.3 and has been shown to be critical in embryonic neurogenesis and neuronal cell fate . SOX‐11 gene mutations have also been previously associated with malignancies such as mantle cell lymphoma and gliomas . More recently, SOX‐11 messenger RNA has shown to be consistently increased in SPNs by RNA microarray analysis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tried to correlate the expression of these markers with GBM patient prognosis, but no consistent associations have currently been established [136]. For example, some studies report an association between CD133, Nestin, cJun, CD44 and ID1 expression and GBM patient poor prognosis [10, [119][120][121]135,137], while others suggest an association of CD133 and SOX-11 expression with longer prognosis [24,122]; other studies report no effects on GBM patient survival due to the expression of Nestin, CD133 and CD15 [138,139]. The contradictory findings regarding the clinical relevance of these putative stem cell markers in GBM warrants further investigation.…”
Section: Other Putative Prognostic Factorsmentioning
confidence: 99%